Mage-Image-Imaginaire - Verbrugghen, Jo (Sint-Martens-Latem : Georges Buysse Gallery, 1974)
Bogaerts, Gaston ; Claerhout, Jef ; Delescluze, Edmond ; De Vuyst, Gaspard ; D'Have, Camille ; Dufoor, Frédéric ; Ghobert, Bernard ; Laurence, Viviane ; Matthijs, Lode ; de Matchwa, Militch ; Monteyne, Roland ; Pasque, Aubin ; Pasternak, Mony ; Perot, Luc ; Rhaye, Yves ; Rolet, Christian ; Salentiny, Jeanne ; Tapta ; Ubrin Choffray, Francine ; Zaboklicka Budzichowa, Maria ; Ensor, James ; Spilliaert, Léon
Mage-Image-Imaginaire, Georges Buysse Gallery, Sint-Martens-Latem, 24 mei tot 31 juli 1974
boek